Characterization of the pyrolysis products of methiopropamine. Issue 7 (25th October 2013) - Bouso, Emily D.; Gardner, Elizabeth A.; O'Brien, John E.; Talbot, Brian; Kavanagh, Pierce V.; Brandt, Simon D.
<x xml:space="preserve">Abstract</x> 1‐(Thien‐2‐yl)‐2‐methylaminopropane (methiopropamine, MPA), appeared as a 'legal high' in late 2010. It is structurally similar to methamphetamine, with a thiophene ring replacing the benzene moiety. Methiopropamine reportedly retains the pharmacological properties of amphetamine stimulants, but it does not fall under existing drug laws in the USA and Ireland. The objective of this research was to identify the pyrolysis products formed under conditions that mimic those used by recreational drugs users. Thirteen pyrolysis products were identified and ten were confirmed by comparison to synthesized standards. Methods for synthesizing the standards as well as an alternative method for the synthesis of methiopropamine were developed. The MPA pyrolysis products are formed through N‐dealkylation, N‐alkylation, N‐formylation, β‐carbon oxidation, β‐carbon oxidation/N‐alkylation, amine elimination and carbon‐carbon bond cleavage. Two pyrazine isomers also formed. Some of these products have the potential to be psychoactive while others are potentially toxic. Copyright © 2013 John Wiley & Sons, Ltd.